The Analysis of The Lesson Plan Based 2013 Curriculum Designed by The English Teacher At MTS Al Hidayah Makassar - Afdaliah Amin (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2021)
This research discusses Analysis of the lesson plan based 2013 curriculum designed by the English teacher at MTS. Al – Hidayah” This research will cover how the English teacher designs learning activities relate with the basic competence to basic competence, and how English teacher do assessment to the students based on 2013 curriculum objectives. This research applied a qualitative research design. The subjects of this research were English teachers in Mts Alhidayah Makassar. Sample of the researcher took two English teachers in Mts Alhidayah Makassar, since there are two English teachers in the school. In collecting the data, the researcher used two kinds of instruments. In collecting the data through interview. Research results show dealing with finding out the basic competence and learning activities, it was that found some of learning activities are related and non related with the basic competences in 2013 curriculum for Junior High School which designed by the English teachers. In learning assessment, the teacher applied various kinds of assessment for cognitive and psychomotor domain. Teachers’ way in assessing students’ achievement in terms of cognitive and psychomotoric based on 2013 curriculum is applying instrument assessment